2022
DOI: 10.1186/s12974-021-02339-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid findings in COVID-19: a multicenter study of 150 lumbar punctures in 127 patients

Abstract: Background Comprehensive data on the cerebrospinal fluid (CSF) profile in patients with COVID-19 and neurological involvement from large-scale multicenter studies are missing so far. Objective To analyze systematically the CSF profile in COVID-19. Methods Retrospective analysis of 150 lumbar punctures in 127 patients with PCR-proven COVID-19 and neurological symptoms seen at 17 European university cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
90
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 100 publications
18
90
1
5
Order By: Relevance
“…In sum, high progranulin CSF levels and low cytokine CSF/serum ratios together may point at a brain in a defensive state against the inflammatory storm coming from the blood. The specific protein results on their own may explain the normal CSF routine parameter measured here and in other studies (14, 28, 29) going along with neurological symptoms as these small concentrations are possibly able to initiate a weak response of the brain.…”
Section: Discussionsupporting
confidence: 70%
“…In sum, high progranulin CSF levels and low cytokine CSF/serum ratios together may point at a brain in a defensive state against the inflammatory storm coming from the blood. The specific protein results on their own may explain the normal CSF routine parameter measured here and in other studies (14, 28, 29) going along with neurological symptoms as these small concentrations are possibly able to initiate a weak response of the brain.…”
Section: Discussionsupporting
confidence: 70%
“…In line with other studies (22), we found elevated CSF glucose and lactate levels in class III patients. Indeed, patients suffering from diabetes were more prevalent in class III (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…CSF was taken in 11 patients. In accordance with a recently published study about CSF findings in COVID-19 [ 9 ], eight of our patients showed blood brain barrier (BBB) dysfunction and all yielded normal cell counts and negative PCR for common pathogens including SARS-CoV-2. Furthermore, nine patients displayed either low-titer antineuronal antibodies in serum (Myelin, CASPR2, NMDAR, Yo), or IgG binding of unknown specificity in indirect immunofluorescence of blood and CSF on unfixed murine brain sections, or both (Table 3 ).…”
supporting
confidence: 91%